Knowledge, awareness, and perception towards tuberculosis disease among International Islamic University Malaysia students. - Thandar Soe, Sumaiyah Jamaludin; Ismail, Nurhanis; Saidi, Sanisah; Hassan, Masmunaa (2018)
Introduction: The increasing of TB cases in Malaysia, raising a question whether the community are equipping themselves with TB knowledge, whether they are aware about TB disease, or having good perception towards TB disease. In order to stop TB disease, community especially health care students need to equip themselves with basic knowledge on TB disease and having good perception towards TB disease. Therefore, there is still inadequate significant finding that show association between level of knowledge and perception of healthcare students on TB disease. Objective: To survey the knowledge, awareness, and perception of International Islamic University Malaysia (IIUM), Kuantan campus students towards TB disease. Methods/Materials: A cross-sectional study was done in six Kulliyyah in IIUM Kuantan campus using a self-administered questionnaire adopt from previous studies within March until May 2018. After obtaining of ethical approval, data was collected. Then, data was analysed using SPSS version 20.0. Result: Relatively low knowledge and awareness (73.8%) and high stigma (67.9%) about TB disease was found among IIUM Kuantan students. Significant association was found between type of Kulliyyah and level of knowledge and awareness. The level of TB perception does not have any significant association with level of knowledge and awareness of TB disease. Conclusion: More efforts should be made to improve the knowledge, awareness, and perception of students regarding TB disease. Hopefully, this study can be a benchmark for other future studies.